PENGARUH MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENYIMAK SISWA PADA PELAJARAN BAHASA INDONESIA DI KELAS V MI MA’HAD AL-ZAYTUN - Dinatu Salma; Dewi Utami; Dede Indra Setiabudi (STKIP Subang, 2024)
Listening is one of receptive skill that must be mastered by the students. They can communicate better when they have good listening skill. However, there are students of primary school encounter some problems in this skill. Therefore, it is important to find alternative solutions that can improve students' listening skills. The study aims to explore the effect of using audiovisual media on students‘ listening skills and to assess the increase of their average score in Indonesian language learning in class V MI Ma'had Al-Zaytun. This research uses a quantitative approach with a pre-experimental design of one group pretest-posttest design. The research sample consisted of 26 grade V students. Data were collected using test and observation techniques. The study shows that the tcount value (8.870) is greater than the ttable value (2.060), which means that there is a significant effect of the media on students' listening skills. And the average students experience the increase of ability in listening skills after the use of audiovisual media. Keywords: Audiovisual Media, Listening Skills, Indonesian Language